The Antidepressant Effect of Deoiled Sunflower Seeds on Chronic Unpredictable Mild Stress in Mice Through Regulation of Microbiota–Gut–Brain Axis - Lu, Xiaomeng; Qi, Ce; Zheng, Jie; Sun, Mei; Jin, Long; Sun, Jin (Frontiers in Nutrition, 2022)
Objectives: Sunflower seeds provide tryptophan-rich proteins with the potential to protect against depression. Tryptophan is a precursor of serotonin and a substrate for the production of indole derivatives by gut microbiota. This study aimed to investigate the association between the depression-alleviating effects of deoiled and dechlorogenic sunflower seeds (DSFS) and regulation of gut microbiota. Methods: Male C57BL/6J mice were fed a diet comprising a source of soy protein (normal and model control), DSFS or whey protein concentrate (positive control) for 7 weeks, and chronic stress-induced depression was induced. Results: Feeding the DSFS diet prevented depression-like behaviors, intestinal barrier damage, elevated plasma corticosterone, and reduced hippocampal serotonin levels in mice. Meanwhile, Feeding the DSFS diet significantly altered the gut microbiota structure, characterized by elevated relative abundances of Ileibacterium valens, Ruminococcus flavefaciens, Clostridium scindens and Olsenella massiliensis, which were inversely associated with depressive behaviors and markers of mucosal barrier damage. DSFS also altered the gut metabolite profile, prevented depression-induced gut L-tryptophan depletion, and upregulated its metabolite indoleacetaldehyde. Conclusions: Feeding the DSFS diet prevented depression in mice by remodeling the gut microbiota and bacterial tryptophan metabolism.